2008
DOI: 10.1063/1.2917253
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent quantum dynamics study of the Ne+H2+(v=–4)→NeH++H proton transfer reaction

Abstract: The Ne + H2+-->NeH+ + H proton transfer reaction was studied using the time dependent real wave packet quantum dynamics method at the helicity decoupling level, considering the H2+ molecular ion in the (v=0-4, j=0) vibrorotational states and a wide collision energy interval. The calculated reaction probabilities and reaction cross sections were in a rather good agreement with reanalyzed previous exact quantum dynamics results, where a much smaller collision energy interval was considered. Also, a quite good ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 36 publications
11
56
0
Order By: Relevance
“…Bartl et al (2013) recently observed HeH2 + , in addition to "all conceivable combinations of n and x" for HenHx + , in mass spectrometry experiments, indicating that these Ng-H2 + structures are likely stable minima, as well. Gamallo et al (2013) studied the reaction of Ne + H2 + and found that the global minimum on the PES is actually NeH2 + following work on this same surface from Mayneris et al (2008). Several studies have explored the interaction of argon atoms and atomic cations with hydrogen molecules and molecular cations (Bedford & Smith 1990;Tosi et al 1993;Song & Gisalson 2003) where most of these build on the seminal work by Adams et al (1970) where noble gas dimers were reacted with hydrogen molecules.…”
Section: Searches For the Related Hehmentioning
confidence: 99%
“…Bartl et al (2013) recently observed HeH2 + , in addition to "all conceivable combinations of n and x" for HenHx + , in mass spectrometry experiments, indicating that these Ng-H2 + structures are likely stable minima, as well. Gamallo et al (2013) studied the reaction of Ne + H2 + and found that the global minimum on the PES is actually NeH2 + following work on this same surface from Mayneris et al (2008). Several studies have explored the interaction of argon atoms and atomic cations with hydrogen molecules and molecular cations (Bedford & Smith 1990;Tosi et al 1993;Song & Gisalson 2003) where most of these build on the seminal work by Adams et al (1970) where noble gas dimers were reacted with hydrogen molecules.…”
Section: Searches For the Related Hehmentioning
confidence: 99%
“…The reactions between atom and molecular ion, such as He, Ne, Ar + normalH2+, have now been extensively studied both experimentally and theoretically . In particular, the Ne + normalH2+ reaction has been paid particular attention over 30 years and most earlier PESs for this reactive system were constricted to the collinear reaction surface .…”
Section: Validities Of the Cs Approximations: Examples And Discussionmentioning
confidence: 99%
“…Huarte-Larrañaga et al [5,6] determined the energy dependence of the state-to-state and state-to-all integral cross section using the exact close-coupling hyperspherical. Mayneris et al [7] determined the Ne þ H þ 2 = Ne þ HD þ =Ne þ HT þ reaction probabilities and cross sections over a wide range of collision energy intervals using a time-dependent real-wave-packet (RWP) quantum calculation. Mayneris-Perxachs et al [8] conducted time-dependent RWP quantum dynamics at the centrifugal sudden level (CS-RWP method), studying the influence of the vibrational excitation of H þ 2 and D þ 2 on the dynamics at thermal collision energies.…”
Section: Introductionmentioning
confidence: 99%